Associations between UGT1A1, SLCO1B1, SLCO1B3, BLVRA and HMOX1 polymorphisms and susceptibility to neonatal severe hyperbilirubinemia in Chinese Han population - Juan Fan; Hua-Yun He; Huan-Huan Li; Pi-Liu Wu; Lei Tang; Bo-Yin Deng; Wen-Hui Dong; Jian-Hui Wang (BMC, 2024)
Abstract Background Severe neonatal hyperbilirubinemia could lead to kernicterus and neonatal death. This study aimed to analyze the association between single nucleotide polymorphisms in genes involved in bilirubin metabolism and the incidence of severe hyperbilirubinemia. Methods A total of 144 neonates with severe hyperbilirubinemia and 50 neonates without or mild hyperbilirubinemia were enrolled in 3 institutions between 2019 and 2020. Twelve polymorphisms of 5 genes (UGT1A1, SLCO1B1, SLCO1B3, BLVRA, and HMOX1) were analyzed by PCR amplification of genomic DNA. Genotyping was performed using an improved multiplex ligation detection reaction technique based on ligase detection reaction. Results The frequencies of the A allele in UGT1A1-rs4148323 and the C allele in SLCO1B3-rs2417940 in the severe hyperbilirubinemia group (30.2% and 90.6%, respectively) were significantly higher than those in the controls (30.2% vs.13.0%, 90.6% vs. 78.0%, respectively, both p < 0.05). Haplotype analysis showed the ACG haplotype of UGT1A1 were associated with an increased hyperbilirubinemia risk (OR 3.122, p = 0.001), whereas the GCG haplotype was related to a reduced risk (OR 0.523, p = 0.018). Conclusion The frequencies of the A allele in rs4148323 and the C allele in rs2417940 are highly associated with the incidence of severe hyperbilirubinemia in Chinese Han neonates. Trial registration Trial registration number:ChiCTR1800020424; Date of registration:2018-12-29.